Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1080/00034989859258
|View full text |Cite
|
Sign up to set email alerts
|

Do the diminishing efficacy and increasing toxicity of sodium stibogluconate in the treatment of visceral leishmaniasis in Bihar, India, justify its continued use as a first line drug? An observational study of 80 cases

Abstract: Eighty parasitologically confirmed cases of visceral leishmaniasis (kala-azar) in Bihar, India, were treated daily with 20 mg sodium stibogluconate/kg for 30 days, to assess the current efficacy and toxicity of this 30-day regimen. Clinical and parasitological cure was obtained in 48 (60%) of the patients. However, 26 (33%) patients did not respond to the first course of treatment (primary unresponsiveness), two relapsed after initial clinical and parasitological cure, and two were withdrawn from the study (on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…However, the drug has unpredictable toxicity [5], [6] and the requisite 4-week hospitalization imposes a huge economic burden on poor families [7]. In addition, high treatment failure to SSG has been identified in some endemic areas with an incidence of up to 60% in some regions of Bihar, India [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the drug has unpredictable toxicity [5], [6] and the requisite 4-week hospitalization imposes a huge economic burden on poor families [7]. In addition, high treatment failure to SSG has been identified in some endemic areas with an incidence of up to 60% in some regions of Bihar, India [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although drugs (mainly antimonials such as sodium stibogluconate [SSG]) currently exist to treat this parasitic infection, their use has been limited because of high cost, toxicity, or development of parasite resistance [3][5]. A multi-center phase III study in India showed that PM is a very efficacious, affordable, and safe treatment [6], and is now registered for VL treatment in India.…”
Section: Introductionmentioning
confidence: 99%
“…However, since this method failed in 30% of the cases,[6] in 1984, the World Health Organization proposed the dosage to be increased to 20 mg/kg/day (maximum: 850 mg) for 20 days. [7] Resistance of Leishmania species to antimonial drugs has alarmingly increased during the past decades. [89]…”
Section: Introductionmentioning
confidence: 99%